Pengaruh Suhu dan Lama Penyimpanan terhadap Penurunan Kadar Vitamin C Brokoli (Brassica oleracea L) - Safaryani, Nurhayati; Haryanti, Sri; Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
The aim of research is to find out the effect of temperature and long storage against decreasing vitamin C degree and was lower decreated vitamin. Randomized Complete Design base on was split plot design 4 x 2 with 3 replicates we used to experiment. First factor was temperature 00 C, 50 C, 100 C and 300 C (Control). Second factor was long storage 3 days and 7 days. The parameters was decreasing vitamin C (%) degree. Data resulted from this research was anova analysis, when there is real difference Duncan test will be used upon significant of 5 %. The result of the decreasing indicated that was a positive interaction betweentemperature and long storege against decreating vitamin C degree. Decreasing vitamin C lower degree on temperature 50 C long storege 3 days was rate 0,004%.